INVENTORY MODEL DEVELOPMENT FOR MEDICINES WITH CONSIDERING LIFETIME, JOINT REPLENISHMENT AND SUBSTITUTE PRODUCTS - Siregar, Meiliana
Medicines are products that have a fixed lifetime and marked by an expiration date. Based on the Republic of Indonesia Minister of Health Regulation No. 73 concerning Pharmaceutical Services Standards in Pharmacy the implementation of pharmacy in pharmacies industry must ensure the availability of safe, quality, useful and affordable medicines. To achieve this, a well-planned inventory is required so there will be nor inventory shortage, neither excess products. In the procurement planning activity, the order lot size is determined which can minimize the total cost of inventory. In this study, the determination of inventory policy was carried out by building a new inventory model by combining several concepts from separate studies, namely lifetime, product substitution, and joint replenishment. The reference model being used is an inventory model for materials which have limited lifetime as explained by Hidayat and Fauzi (2015) and concurred by the model by Chairunnisa (2018) and also joint replenishment model with substitusion (JRMS) by Salameh, et al. (2014). The proposed inventory model accommodates two types of medicines that are in the same category where both medicines have a fixed lifetime and features the same function and composition of active substances. The supply of both medicines may run out due to demand or lifetime and under a versatile substitution model where every medicine in-stock can partially substitute a stocked-out medicines. In addition, medicines in the same category are ordered collectively in each order cycle in order to achieve efficiency in holding costs and ordering costs from joint replenishment. The proposed model optimizes ordering quantities for each medicine with the objective of minimizing the total cost associated with the setup costs, holding costs, shortage costs, and expiration costs. The solution procedure of the proposed model is performed by analyzing the calculation results of 2 scenarios where at this stage the medicine that will act as a substitute for other drugs is selected, which is then followed by case determination. Determination of cases is selected based on the reason the medicine supply runs out, if due to demand it is classified in case 1 and if due to lifetime it is classified as case 2. When the inventory problem is classified in case 2 then an additional evaluation will be performed, namely calculating the total cost of the inventory from the inventory policy after adjustments are made then compare it with the total cost of inventory without adjustment or case 1. If the total cost of inventory resulting from case 1 is better than case 2 then the inventory policy will be used and vice versa. Based on trials conducted on 30 medicine groups, it was found that the inventory policy of 28 medicine groups was the result without adjustment, namely 17 drug groups were completed with scenario 2 cases 1 and as many as 11 drug groups were completed with scenario 1 case 1 while the rest were the results with adjustments where the results of scenario 1 case 1 provide better performance criteria than scenario 2 case 2. In addition, the proposed model provides a better expectation of total inventory costs than the current pharmacy inventory policy. This policy provides a total inventory cost expectation of Rp 18,836,919 per month for 60 types of medicines managed by pharmacies. This policy resulted in a savings in message costs by 28%, savings in saving costs by 85%, savings in the cost of deficiencies by 98%, and savings in expiration costs by 100% compared to the costs resulting from the current policy. This cost savings can be obtained as the proposed model considers the lifetime and application of the concept of substitute products and joint replenishment that is able to maximize the use of each type of medicine so as to reduce inventory costs in the form of reduced message costs, storage costs, reducing expectations of the amount of drug shortage and avoiding the availability of expired products.